2022
DOI: 10.1042/bsr20212808
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RIP3 increased ADSC viability under OGD and modified the competency of adipogenesis, angiogenesis, and inflammation regulation

Abstract: Adipose-derived stem cells (ADSCs) showed decreased cell viability and increased cell death under oxygen-glucose deprivation (OGD). Meanwhile, vital necroptotic proteins, including receptor-interacting protein kinase (RIP) 3 and mixed lineage kinase domain-like pseudokinase (MLKL), were expressed in the early stage. This study aims to explore the effect of necroptosis inhibition on ADSCs. ADSCs were obtained from normal human subcutaneous fat and verified by multidirectional differentiation and flow cytometry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
(44 reference statements)
1
8
0
Order By: Relevance
“…In this study, PPARγ was also negatively correlated with hepatic RIPK3 in patients with NAFLD ( Afonso et al., 2021 ). Moreover, the inhibition of RIPK3 using a Glaxo Smith Kline inhibitor increased the expression of PPARγ as well as triglyceride accumulation in ASC ( Yang et al., 2022 ). Thus, RIPK3 appears as a lipid metabolism regulator, which activity might be targeted ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, PPARγ was also negatively correlated with hepatic RIPK3 in patients with NAFLD ( Afonso et al., 2021 ). Moreover, the inhibition of RIPK3 using a Glaxo Smith Kline inhibitor increased the expression of PPARγ as well as triglyceride accumulation in ASC ( Yang et al., 2022 ). Thus, RIPK3 appears as a lipid metabolism regulator, which activity might be targeted ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that IVD-like low-glucose conditions may be a positive factor for MSC transplantation in the treatment of IDD, while too low concentrations of glucose can have significant negative effects. Recently, Yang et al [109] further studied and found that oxygen-glucose deprivation AD-MSCs: adipose-derived mesenchymal stem cells; AF-MSCs: amniotic fluid-derived mesenchymal stem cells; BMSCs: bone marrow-derived mesenchymal stem cells; ECM: extracellular matrix; IL-1β: interleukin-1β; IVD: intervertebral disc; NP: nucleus pulposus; NP-MSCs: nucleus pulposus-derived mesenchymal stem cells; PB-MSCs: peripheral blood-derived mesenchymal stem cells; PMSCs: placenta-derived mesenchymal stem cells; SMSCs: synovialderived mesenchymal stem cells; TGF: transforming growth factor; UC-MSCs: umbilical cord-derived mesenchymal stem cells.…”
Section: Nutrient Deficiency Ivd Cells Are Supplied With Essentialmentioning
confidence: 99%
“…These results suggest that IVD-like low-glucose conditions may be a positive factor for MSC transplantation in the treatment of IDD, while too low concentrations of glucose can have significant negative effects. Recently, Yang et al [ 109 ] further studied and found that oxygen-glucose deprivation not only significantly inhibited the viability and adipogenesis of AD-MSCs but also inhibited cell proliferation and migration. Inhibition of receptor-interacting protein kinase-3 (RIP3) increased the viability, proliferation, and migration of AD-MSCs under oxygen-glucose deprivation and reduced unstable neovascularization and inhibited inflammatory responses [ 109 ].…”
Section: Influence Of the Ivd Microenvironmental Factors On Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…When ADSCs are deprived of oxygen and glucose, some studies have demonstrated that ADSCs might regulate survival potential and stemness through autophagy ( Li et al, 2017 ; Yang et al, 2021 ). In our previous study, a preexperiment was carried out, and we developed an OGD model to imitate the hypoxic and glucose-free environment in vivo ( Yang et al, 2022 ). We also regulated RIP3, a key target in necroptosis, to relieve the effect of OGD treatment.…”
Section: Introductionmentioning
confidence: 99%